2022
DOI: 10.1007/s00417-022-05739-x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective, multicenter study on the management of macular holes without residual internal limiting membrane: the refractory macular hole (ReMaHo) study

Abstract: Purpose To evaluate the surgical management, outcomes and prognostic factors of full thickness macular holes without residual internal limiting membrane (NO-ILM FTMHs). Methods We performed a multicenter, retrospective study of 116 NO-ILM FTMHs. Human amniotic membrane (hAM) plug, autologous ILM free flap transplantation (AILMT), and autologous retinal graft transplantation (ART) were performed in 58, 48, and 10 patients, respectively. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some studies have reported that BCVA with MHRD after surgery was related to preoperative visual acuity. 17,18 We found that BCVA improvement after MH sealing was not associated with corrected MH diameter, axial length, age, or sex. We attributed our results to the following point: patients with MHRD had atrophic myopic maculopathy in different scales, retinal choroidal and outer retinal layer atrophy should be considered when evaluating the postoperative vision recovery.…”
Section: Discussionmentioning
confidence: 78%
“…Some studies have reported that BCVA with MHRD after surgery was related to preoperative visual acuity. 17,18 We found that BCVA improvement after MH sealing was not associated with corrected MH diameter, axial length, age, or sex. We attributed our results to the following point: patients with MHRD had atrophic myopic maculopathy in different scales, retinal choroidal and outer retinal layer atrophy should be considered when evaluating the postoperative vision recovery.…”
Section: Discussionmentioning
confidence: 78%
“…Successful closure of large, refractory, or recurrent MH where ILM is missing has been achieved with the use of AM grafts [15]. Because the AM graft should be placed under the edges of the MH, with the chorion/stromal side facing the RPEs, careful placement of AM can be challenging [16][17][18][19][20]. Table 1 summarizes the previous studies on the surgical management of MH in Alport patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some FTMHs remain open after primary surgery (refractory), or they reopen after initial closure (recurrent), necessitating secondary surgery. Secondary closure proves successful in over 75% of patients, not often leading to substantial visual improvement [27].…”
Section: Refractory and Recurrent Casesmentioning
confidence: 99%